AN ANALYSIS OF THE PASSIVE VOICE IN REPORT TEXTS WRITTEN BY STUDENTS AT ELEVENTH GRADE OF SMA NEGERI 5 PALANGKA RAYA - Bahing, Bahing; Mayang Meilantina; Misrita, Misrita (Journal of Innovation Research and Knowledge, 2024)
This research was highly concerned with the study of passive voice made by the students at SMA Negeri 5 Palangka Raya. It was an analysis of the passive voice in report texts made by the students of eleventh grade Students in SMA Negeri 5 Palangka Raya. In this case, the analysis was to find out the use of passive voice which was regarded as incorrect forms in report texts of SMANegeri 5, Palangka Raya, especially in XI-IPS class. This research applied the descriptive Qualitative as the research method. The researcher collected the data by provided the students with the writing tasks and questionnaire as an instrument to the subjects. In processing the data obtained, this research followed the data processing procedure, such as collecting, identifying, classifying, coding, and tabulating. Then, the data were analyzed and described into the conclusion of the research. The result of data analysis showed that the students of SMA Negeri 5 Palangka Raya, particularly in eleventh grade have difficulties in using passive voice when they made report texts, which consisted of passive voice formula. The analysis showed that from 44 incorrect sentences that the students have made. There were total 75 incorrectness divided into percentage first, incorrectness in tense 52 %. Second, incorrectness in auxiliaries to be 24 %, And lastly, incorrectness in past participle form 24 %. And there were included in 39 incorrectness in tense, 18 incorrectness auxiliary be, and 18 incorrectness in past participle form. Thus, the researcher concluded that based on the data of the first and second task, the result of questionnaire, it showed that the eleventh grade students of SMA Negeri 5 Palangka Raya still did not understand fully how to use passive voice in providing the Report Text.